An exploration of diabetic foot screening procedures data by a multiple correspondence analysis - Urbančič Rovan, Vilma; Rovan, Jože (Zdravstveno varstvo, 2017)
Gangrene and amputation are among most feared complications of diabetes mellitus. Early detection of patients at high risk for foot ulceration can prevent foot complications. Regular foot screening (medical history, foot examination and classification into risk groups) was introduced at the out-patient diabetes clinic in Ljubljana in November 1996. We aimed to explore the relationships between the observed variables, check the appropriateness of the risk status classification and of the post-screening decisions. The data of 11.594 patients, obtained in 18 years, were analysed by multiple correspondence analysis (MCA). Most of the observed variables were categorical. The majority of the screened population was free of foot complications. We demonstrated an increasing frequency and severity of foot problems with an increasing age, as well as the association between the loss of protective sensation and the history of foot ulceration, foot deformity and callus formation, the history of foot ulcer or amputation and acute foot ulceration. A new finding was that the location of foot deformity points was closer to female than male gender, indicating the possible role of fashionable high-heel footwear. The appropriateness of therapeutic decisions was confirmed: the points representing absent foot pulses and referral to vascular specialist were close together, as well as points representing foot deformity and special footwear prescription or callus formation and referral to pedicurist. MCA was applied to the data on foot pathology in the population attending the out-patient diabetes clinic. The method proved to be a useful statistical tool for analysing the data of screening procedures.